2014
DOI: 10.1007/s13197-014-1333-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of grape seed powder on oxidative stability of precooked chicken nuggets during frozen storage

Abstract: The inhibitory effect of grape seed powder (GSP) on lipid oxidation in chicken nuggets during frozen storage for 5 months was investigated. Chicken nuggets were prepared by dipping into batter containing GSP and pre-fried at 180°C and then stored at −18°C. Prefried chicken nugget crusts showed antioxidant properties. Primary oxidation products, determined by the peroxide value (POV) and conjugated diene (CD) concentration, gradually increased until month 2 and then declined, which is an indication of secondary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 49 publications
2
15
0
Order By: Relevance
“…In Figure 3A, it was observed that SS formulation accumulated higher amount of peroxide in 90 days of freezing, followed by a drop at 135 days of storage, which probably occurred due to the degradation of hydroperoxides into secondary oxidation products. PI values in chicken sausages were below the limit of perceived of rancidity over the storage period, and Cagdas and Kumcuoglu (2015) refer to this limit of perception as being ≥10 mEqO 2 /kg.…”
Section: Resultsmentioning
confidence: 99%
“…In Figure 3A, it was observed that SS formulation accumulated higher amount of peroxide in 90 days of freezing, followed by a drop at 135 days of storage, which probably occurred due to the degradation of hydroperoxides into secondary oxidation products. PI values in chicken sausages were below the limit of perceived of rancidity over the storage period, and Cagdas and Kumcuoglu (2015) refer to this limit of perception as being ≥10 mEqO 2 /kg.…”
Section: Resultsmentioning
confidence: 99%
“…A significant decrease in redness value of both nuggets during storage was corresponded to protein denaturation/concentration, fat and water content, meat pigments and degree of oxidative reactions (Devatkal et al 2014). During frozen storage, malonaldehyde, an oxidative product generated by lipid oxidation, can react with myosins, resulting in the discoloration of stored meat products (Cagdas and Kumcuoglu 2015).…”
Section: Colormentioning
confidence: 99%
“…Wine pomace products have been applied in meat products from different species such as beef (Ahn and others , ), pork (Carpenter and others ; Sasse and others ), chicken (Shirahigue and others ), turkey (Mielnik and others ), goat (Rababah and others ), and buffalo (Tajik and others ), usually in patties or sausages that permit an acceptable homogeneity of the product in the matrix (Ryu and others ; Liu and others ; Wagh and others ). In the case of intact muscles (such as chicken breasts or steaks), the products can be applied by pressurized tumbling (Rababah and others , ), by rubbing with the dehydrated product (Wong and Kitts ), by dipping the meat product into a mix or solution containing the antioxidant (Vaithiyanathan and others ) such as frying batters (Cagdas and Kumcuoglu ) and marinades (Gibis and Weiss ), and by spraying the antioxidant onto the surface of the meat (Camo and others ). Other meat products that have been tested include liver (Pateiro and others ), restructured mutton (Reddy and others ), chorizo (Lorenzo and others ), pâté (Pateiro and others ), dry‐cured bacon (Wang and others ), mortadella‐type sausages (Moradi and others ), and Milano‐type salami (Mendes and others ), as well as dehydrated meat (Nissen and others ) and lard (Schevey and Brewer ).…”
Section: Functions In the Food Industrymentioning
confidence: 99%